Potential Use of Chilean Native Species in Vertical Greening Systems - Mitsi, C (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Vertical greening systems (VGSs), i.e., living walls (LWs) and green façades (GFs), are considered a promising technology to diminish the negative effects of urbanisation. Plant selection for these systems is challenging due to the narrow spectrum of species available, and the required adaptation to specific climate conditions. Considering Chile’s rich plant biodiversity, this study aims to analyse the potential of Chilean native species to be introduced in VGSs. A total of 109 potentially usable species from the north (n = 25), centre (n = 32), south (n = 31) and the Andes Mountains (n = 21) were selected for VGSs, showing a high level of endemism (43.1%). According to the filters applied, 39 and 70 species were selected for GFs and LWs, respectively. To evaluate appreciation of Chilean native plants and their potential use in VGSs, an online questionnaire was responded by 428 individuals. Most participants agreed or strongly agreed with the use of LWs and/or GFs inside their house/apartment (75.5%) and in their garden/balcony (90.0%). Most of the participants agreed or strongly agreed with the use of Chilean native plants inside their house/apartment (75.0%) and in their garden/balcony (84.4%). Further empirical studies are still required to confirm the use of Chilean native species in LWs and GFs. © 2023 by the authors.